Methane production by three widespread marine phytoplankton species: release rates, precursor compounds, and potential relevance for the environment [dataset] - Klintzsch, Thomas; Keppler, Frank (Universität, 2019)
We investigated marine algae as a source of methane (CH4) in oxic surface waters of oceans. The widespread haptophytes Emiliania huxleyi, Phaeocyst...